Gadget dan Perkembangan Sosial Anak Usia Dini - Delpima Suhita; Melinedri Melinedri; Tika Meldina; Yulya Muharmi; Nella Novita (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
Gadgets are a result of the development of information technology. Gadgets are multi-functional media that are not only used as a medium of communication but also as a medium of information and recreation. With this small device, a wireless gadget can be carried and used anywhere. Not a few people are addicted to gadgets, including children. This dependence can be caused because gadgets help in work, it can also be due to dependency due to hobbies so that it becomes "addictive". Social development must be honed from an early age. It will be an obstacle if children prefer to play with gadgets, because it will reduce children's interactions with parents, siblings, peers, or other people. Social development in children will not be optimal due to the lack of interaction. Here, parenting styles from parents are needed in managing the use of gadgets in children